Strategies Used by English Teachers to Encourage Students to Speak at Alam Mutiara Insan Sorong Junior High School Grade VII - Alfian Dian Rafika; Abd. Rahman; Miftahulfadlik Dabamona (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research focuses on strategies used by English Teachers to Encourage Students to Speak at SMP Integrated Islamic Junior High School Class VII. The purpose of this research is to analyze the strategies used by English teachers to encourage students to speak in front of grade VII of SMP IT Mutiara Insan Sorong. This research uses a qualitative method with a data collection process through observation, interviews, and documentation. The findings of this study prove that the strategies used by English teachers have the goal of training students' development. The strategies used are 1) a fun differentiation method to attract students' attention. 2) Diagnostic assessment method, which is to understand the condition of students because they have various learning styles. 3) Evaluate and provide additional materials so that the value is higher. 4) Increase the number of students' vocabulary. However, in achieving some of these strategies, teachers experience obstacles so that they do not reduce optimization to students and have a positive influence on the encouragement to speak English fluently and confidently.